Best-Beta CAPM (BCAPM) Optimal Portfolio Performance Using EROV, Sortino, and M2 Methods - Abdul Aziz; Mohammad Farhan Qudratullah (Kaunia: Integration and Interconnection Islam and Science Journal, 2021)
This study discusses the optimal portfolio performance analysis using Best-Beta CAPM (BCAPM) with methods EROV, Sortino, and M2 were applied to stocks sharia incorporated the Jakarta Islamic Index (JII) in the period from October 1, 2014 – August 31, 2017. The results obtained from this study C portfolio showed an optimal portfolio. The proportion of each stock included in the optimal portfolio is stock UNTR (95.27%) and AKRA (4.73%) with a rate of return expected from optimal portfolio is 1.39%, while the risk of an optimal portfolio of 0.066%. Result of consistency test between the performance of stock portfolio with Kendall’s tau test showed that that those methods was consistent in assessing the performance of stocks portfolio.